Intel Xeon Phi Coprocessor High Performance Programming : James Jeffers, James Reinders Morgan Kaufmann, 2013 ISBN-13: 978-0124104143 - More, Andres (2013)
James Reinders (Chief Evangelist of Intel® Software at Intel) and Jim Jeffers (Principal Engineer at Intel) have gathered in this book the working knowledge of the people involved to prototype and productize the Intel® Xeon Phi coprocessor. This include the experience of Intel’s Product, Field, Application and Technical Consulting Engineers, as well as key partners involved on product pre-release work.